Ferromagnetic Enhancement in LaMnO3 Films with Release and Flexure (Adv. Mater. Interfaces 24/2021). Issue 24 (22nd December 2021) - Yao, Hongbao; Jin, Kuijuan; Yang, Zhen; Zhang, Qinghua; Ren, Wenning; Xu, Shuai; Yang, Mingwei; Gu, Lin; Guo, Er‐Jia; Ge, Chen; Wang, Can; Xu, Xiulai; et al.
Abstract : Ferromagnetic Enhancement in LaMnO3 Films with Release and Flexure In article number 2101499, Hongbao Yao, Kuijuan Jin, and co‐workers report the achievement of doubly‐enhanced magnetization and raised Curie temperature in the freestanding manganite thin films by releasing the misfit strain and introducing the flexure, demonstrating that flexible mechanical modulations provide an extraordinary opportunity to design and manipulate correlated electronic states of functional oxides.